Pedro de Cartagena y otros poetas en el cancionero SA10b: variantes, variaciones y testimonios únicos. - RODADO RUIZ, ANA M. (Scripta)
This paper deals with the study of the textual variants detectable in the works of several poets, collected in the songbook SA10b. My aim is to focus on the singular lessons of this manuscript -often equipollent lessons worthy of analysis-despite the fact that they tend to be discarded in the critical edition of many works, as SA10b is generally situated in the higher branches of the textual tradition. In this paper, I will focus on the study of the poems of Pedro de Cartagena, from whom a large corpus is collected, and of other authors with a scarce presence in SA10b. The peculiar configuration of this collection and the selection of works it contains confirm the relevance of a detailed analysis of textual variants, which will contribute to shed light on the process of transmission of the poems and on the genesis of this songbook.